A decision making framework for procurement method selection for building maintenance projects: The case of public Universities in Malaysia / Shirley Chua Jin Lin - Shirley Chua, Jin Lin (2014)

(untitled)
This thesis presents a study of the selection of procurement method for building maintenance management for public universities in Malaysia through the use of Multiple Criteria Decision Making (MCDM) particularly the Analytic Hierarchy Process (AHP). A large number of different types of procurement methods have been developed to overcome the weaknesses of the existing procurement method and to meet the range of service requirement. Thus, it is more challenging for the decision maker to select the most appropriate procurement method for a specific building as different types of procurement method suit different types of project. It is indeed very vital to develop a systematic approach that can assist the maintenance personnel in decision making on selecting procurement method for a particular building. The study adopted mixed method that is the combination of both qualitative and quantitative method. There were 26 procurement selection criteria identified from literature review that were divided into three main categories that were clients’ requirement, project characteristic and external environment or factor. In addition, there were 13 types of procurements methods identified in literature review. A questionnaire survey was conducted among all public universities in Malaysia with 85 per cent response rate. The finding of this research proves that the selection of procurement methods by university organizations is neither strategic nor systematic as there is no guidance available for the decision maker to rely on in order to select the most appropriate procurement strategy thus provides impetus for this study. Through the questionnaire survey, there were 19 procurement selection criteria which were categorized into 3 main criteria were shortlisted and 4 procurements methods which include outsourcing by specialist term contract, outsourcing by tendered schedule term contract, outsourcing by repair and maintenance contract and outsourcing by measured iv term contract were identified to be the most popular procurement methods adapted by public universities currently (Percent of Cases > 50%) and at the same time were considered most important (mean >4 or almost equal to 4). In addition, these 4 procurements methods obtained mode equals to 4. These procurement selection criteria and alternatives were considered in the development of decision making framework. The decision making framework was developed based on AHP technique and principles. Expert Choice Software was employed as development tool where the shortlisted criteria and alternatives from questionnaire survey were integrated into the framework. Finally, structured interview was conducted to validate the framework developed. The validation process was carried out through structured interview with 9 public universities selected. The evaluations done by the 9 universities revealed that majority of the interviewees perceived that the Decision Making Framework for Procurement Method Selection of Building Maintenance Management for Public Universities developed was good (65%) and excellent (21%) in term of capability, applicability and validity in assisting the decision makers to select the most appropriate procurement method in building maintenance work. The proposed decision making framework introduced expected to be a useful tool for maintenance organization that can assist them in decision making on selecting the most appropriate procurement method.